68. Cerebellar transcranial direct current stimulation modulates pain perception in humans: A laser evoked potentials (LEPS) study. Issue 1 (January 2015) - Bocci, T.; Vannini, B.; Torzini, A.; Giorli, E.; Ferrucci, R.; Carli, G.; Priori, A.; Sartucci, F.
<x xml:space="preserve">Abstract</x> Cerebellum is involved in a wide number of integrative functions, most of them unknown. Particularly, its role in pain processing has only poorly understood. We evaluated the effects of cerebellar transcranial direct current stimulation (c-tDCS) on pain perception by assessing changes in laser evoked potentials (LEPs) parameters (perceptive threshold, N1–N2/P2 amplitudes and latencies) by stimulating the left hand. Materials and Methods: Twelve healthy subjects were enrolled and studied before and after anodal, cathodal and sham tDCS (20', 2.0 mA). LEPs were obtained using a neodymium:yttrium–aluminium–perovskite (Nd:YAP) laser. While cathodal c-tDCS improves amplitudes (N1: F(2, 66) = 23.3, p < 0.0001; N2/P2: F(2, 66) = 19.1, p < 0.0001) and decreases LEPs latencies (N1: F(2, 66) = 7.7, p = 0.001; N2/P2: F(2, 66) = 5.4, p = 0.007) compared with sham condition, anodal c-tDCS elicits opposite effects (p < 0.001 for all the comparisons). Anodal polarization dampens perceptive threshold, while the cathodal stimulation increases it (p < 0.001). The main finding of our study is that cerebellar direct current polarization is able to modulate pain perception in humans. As c-tDCS was effective on N1 and N2/P2 components, we speculate that cerebellum is engaged in pain processing dynamically modulating the activity of both secondary somatosensory and cingulate cortices.